Cognitive and motor deficits in older adults with HIV infection: Comparison with normal ageing and Parkinson's disease. Issue 2 (8th October 2020) - Müller‐Oehring, Eva M.; Fama, Rosemary; Levine, Taylor F.; Hardcastle, Cheshire; Goodcase, Ryan; Martin, Talora; Prabhakar, Varsha; Brontë‐Stewart, Helen M.; Poston, Kathleen L.; Sullivan, Edith V.; Schulte, Tilman
Abstract : Despite the life‐extending success of antiretroviral pharmacotherapy in HIV infection (HIV), the prevalence of mild cognitive impairment in HIV remains high. Near‐normal life expectancy invokes an emerging role for age–infection interaction and a potential synergy between immunosenescence and HIV‐related health factors, increasing risk of cognitive and motor impairment associated with degradation in corticostriatal circuits. These neural systems are also compromised in Parkinson's disease (PD), which could help model the cognitive deficit pattern in HIV. This cross‐sectional study examined three groups, age 45–79 years: 42 HIV, 41 PD, and 37 control (CTRL) participants, tested at Stanford University Medical School and SRI International. Neuropsychological tests assessed executive function (EF), information processing speed (IPS), episodic memory (MEM), visuospatial processing (VSP), and upper motor (MOT) speed and dexterity. The HIV and PD deficit profiles were similar for EF, MEM, and VSP. Although only the PD group was impaired on MOT compared with CTRL, MOT scores were related to cognitive scores in HIV but not PD. Performance was not related to depressive symptoms, socioeconomic status, or CD4 + T‐cell counts. The overlap of HIV‐PD cognitive deficits implicates frontostriatal disruption in both conditions. The motor‐cognitive score relation in HIV provides further support for the hypothesis that these processes share similar underlying mechanisms in HIV infection possibly expressed with or exacerbated by ageing.